Free cash flow, profitabilitas dan dividend payout ratio terhadap nilai perusahaan pada 50 biggest market capitalization - Damayanti, Elsa; Yulianto, Agung; Muna, Arinal (Nur Science Institute, 2024)
Companies with the biggest market capitalization in Indonesia have seen a price decline in book value. This study aims to examine the impact of free cash flow, profitability, and dividend payout ratio on a firm. Value in terms of free cash flow is calculated using the free cash flow ratio. Profitability uses the return on assets ratio and dividend payout ratio using the dividend payout ratio, whilst business value is calculated using the price to book value. The study’s data population comprises the 50 biggest market capitalization businesses listed on the Indonesian Stock Exchange in 2020-2022. Employing purposive sampling as a sample method, as many as 66 samples are available that match the requirements. The analytical technique employed is multiple linear regression analysis, and the secondary data used is obtained from the website www.idx.co.id. According to the study’s findings, free cash flow does not affect a firm value. Firm value is influenced by profitability and dividend payout ratio.